2015
DOI: 10.2175/193864715819540883
|View full text |Cite
|
Sign up to set email alerts
|

A New Membrane-Aerated Biofilm Reactor for Low Energy Wastewater Treatment: Pilot Results

Abstract: A new hybrid membrane-aerated biofilm reactor (MABR) technology that enables energy-neutral treatment of municipal wastewater is introduced. The process, which removes nitrogen using conventional nitrificationdenitrification, was demonstrated at pilot-scale, treating primary effluent. The new MABR membrane product can operate in a high mixed liquor suspended solids (MLSS) environment, making it suitable for use in a conventional activated sludge reactor to increase oxygen transfer and nitrification capacity. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 5 publications
1
7
0
1
Order By: Relevance
“…Cui also got the same result through the experiment [15], that ammonia-oxidizing bacteria activity was suppressed when the water dissolved oxygen content was low, which led to the ammonium oxidation rate reducing; moreover, when the content of dissolved oxygen in water had been recovered, ammonia-oxidizing activity of bacteria would be restored. The results shown in figure 3 and 4 are also consistent with the views of Côté et al [16]. They adopted the MABR of Zeelung fiber to achieve an ammonia nitrogen removal efficiency of 95%.…”
Section: Figure 1 Process Flow Diagram Of a Single Bench-scale Reactorsupporting
confidence: 88%
See 1 more Smart Citation
“…Cui also got the same result through the experiment [15], that ammonia-oxidizing bacteria activity was suppressed when the water dissolved oxygen content was low, which led to the ammonium oxidation rate reducing; moreover, when the content of dissolved oxygen in water had been recovered, ammonia-oxidizing activity of bacteria would be restored. The results shown in figure 3 and 4 are also consistent with the views of Côté et al [16]. They adopted the MABR of Zeelung fiber to achieve an ammonia nitrogen removal efficiency of 95%.…”
Section: Figure 1 Process Flow Diagram Of a Single Bench-scale Reactorsupporting
confidence: 88%
“…This modification not only reduces energy consumption but also increases processing capacity and facilitates future expansion needs. Cote et al in a recent study showed that using ZeeLung™ cords MABR can achieve greater than 6 kg/O2/kWh energy efficiency [8], at the same time remained 91% of the total removal rate of suspended particulate matter, COD removal rate of 83%. 95% ammonia removal rate and 66% total inorganic removal rate for traditional domestic sewage.…”
Section: Introductionmentioning
confidence: 98%
“…It should be noted that aeration control via manipulating the oxygen partial pressure is often not practiced in commercial applications. Instead, oxygen is introduced into the MABR lumen at the design airflow rate, and oxygen partial pressure in the lumen changes as a result of oxygen transfer and microbial consumption (Côté et al 2015;Bicudo et al 2019). For Zeelung and OxyMem MABRs, this is done because exhaust gas from the MABR is used to create fluid flow through the MABR bundle to renew the fluid inside the bundle and to increase the mass transfer of substrates from the bulk liquid into the biofilm on the MABR membranes (Downing 2021).…”
Section: Oxygen Transfer and Aeration Modesmentioning
confidence: 99%
“…The advantages of MABR technology include high effluent quality (Sunner et al 2018;Sathyamoorthy et al 2019), high carbon processing efficiency (Houweling & Daigger 2019;Mehrabi et al 2020), up to 100% oxygen transfer efficiency (OTE) (Heffernan et al 2017;Bicudo et al 2019), and compact reactor footprints (Sunner et al 2018). Compared to other biofilm reactors, like Moving Bed Biofilm Reactor (MBBR) with a typical designed nitrification rate (NR) of 0.5 g N/m 2 -d, MABRs achieve greatly improved NRs of 1.0-3.0 g N/m 2 -d (Côté et al 2015;Kunetz et al 2016;Peeters et al 2017aPeeters et al , 2017bUnderwood et al 2018;Nathan et al 2020). The greatly improved NRs result from high oxygen transfer rates (OTRs) in MABRs.…”
Section: Introductionmentioning
confidence: 99%
“…Bio lm oxygen demand, which is a function of bio lm characteristics and operational parameters such as other substrates concentration (nitrogen and carbon), in uences the oxygen gradient's extent within the membrane wall in a treatment process (Pellicer-Nàcher et al, 2013;Shanahan and Semmens, 2006). The OTR and OTE are calculated as per equations 1 and 2 (Côté et al, 2015):…”
Section: Introductionmentioning
confidence: 99%